2019
DOI: 10.1038/s41598-019-46386-3
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of standard clinical 3T prostate MRI for pelvic lymph node staging: Comparison to 68Ga-PSMA PET-CT

Abstract: The aim was to assess the performance of prostate 3T MRI for pelvic lymph node (LN) staging in prostate cancer (PCa), in comparison to 68 Gallium-prostate specific membrane antigen PET-CT ( 68 Ga-PSMA PET-CT) as reference standard for LN detection. 130 patients with PCa underwent non-contrast-enhanced multiparametric prostate 3T MRI and 68 Ga-PSMA-PET-CT within 180 days at our institution. Overall, 187 LN metastases (n = 43 patients) detected… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Hence, merely in patients with large tumor volumes in mpMRI, 68 Ga-PSMA-PET/CT might give little complimentary information. However, these patients bear a high risk for lymph node or distant metastases [32], and 68 Ga-PSMA-PET shows high sensitivities and specificities for lymph node detection, especially in metastases smaller than 10 mm and thus is beneficial for lymph node staging [33,34]. Consequently, our data encourage the usage of 68 Ga-PSMA-PET and mpMRI for biopsy guidance and planning of focal therapies and show that 68 Ga-PSMA-PET should at least be performed in patients with intermediate and high-risk PCa since it gives highly complementary information.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, merely in patients with large tumor volumes in mpMRI, 68 Ga-PSMA-PET/CT might give little complimentary information. However, these patients bear a high risk for lymph node or distant metastases [32], and 68 Ga-PSMA-PET shows high sensitivities and specificities for lymph node detection, especially in metastases smaller than 10 mm and thus is beneficial for lymph node staging [33,34]. Consequently, our data encourage the usage of 68 Ga-PSMA-PET and mpMRI for biopsy guidance and planning of focal therapies and show that 68 Ga-PSMA-PET should at least be performed in patients with intermediate and high-risk PCa since it gives highly complementary information.…”
Section: Discussionmentioning
confidence: 99%
“…As for imaging modalities, 68 Ga-PSMA-PET for identification of LNI was reported to be more sensitive than 3T-MRI. 21 Furthermore, combination of 68 Ga-PSMA-PET, ISUP biopsy Grade and PI-RADS score by mpMRI was reported to be useful for prediction of LNI. 22 A recent study showed that integration of SUV max by PSMA-PET, the neutrophillymphocyte and platelet-lymphocyte ratios, initial PSA, and clinical T stage served as predictors for LNI diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…As for imaging modalities, 68 Ga‐PSMA‐PET for identification of LNI was reported to be more sensitive than 3T‐MRI 21 . Furthermore, combination of 68 Ga‐PSMA‐PET, ISUP biopsy Grade and PI‐RADS score by mpMRI was reported to be useful for prediction of LNI 22 .…”
Section: Discussionmentioning
confidence: 99%
“…MRI and CT, dependent on morphological assessment of nodal disease, have similar but unfortunately limited levels of performance in detection of metastatic nodal detection [61]. Several PET tracers, including 2-deoxy-2-( 18 F)fluoro-D-glucose, sodium ( 18 F)fluoride, ( 11 C)choline and ( 18 F)choline have been found to perform comparably or worse than MRI and CT for nodal disease, but recent preliminary reports suggest that PET/CT with some (PSMA)-based tracers may permit greater sensitivity without sacrificing specificity [62,63]. Nonetheless in light of the above-mentioned performance for bone metastases, WB-MRI remains attractive alone or in combination with PSMA PET as the clinical significance of the sub-centimetre nodes that are poorly seen with WB-MRI remains to be established.…”
Section: Prostate Cancermentioning
confidence: 99%